Case series : patients with JAK2 positive myeloproliferative neoplasms associated with thrombotic events. - Gálvez, K.; Combariza, J. F.; Olaya, V.; Ballesteros, L. M. (Revista Colombiana de Hematología y Oncología, 2017)
Objective. To identify patients with chronic myeloproliferative neoplasms with JAK2 mutation positive and the presence of thrombosis. To analyze the presence of some symptoms and laboratory parameters, their relation with diagnosis and the presence of thrombosis.